ADEQUABILIDADE, DIVERSIDADE GENÉTICA E ESPÉCIES ASSOCIADAS À Curitiba prismatica (D. Legrand) Salywon & Landrum - Silva, Richeliel Albert Rodrigues (2020)
With the constant climatic changes together with the intensification of fragmentation in the Mixed Ombrophilous Forest (MOF), researches have been demanded to know the autoecology of the native species. In this sense, the objective of the present study was to evaluate the ecological niche, the genetic diversity and the associated species of Curitiba prismatica (murta), an endemic species of MOF. The niche modeling was performed based on the association between the bioclimatic and species occurrence data, considering the current time and the future projection, in the optimistic (RCP4.5) and pessimistic (RCP8.5) scenarios, in the MaxEnt software. For the study of genetic diversity, individuals were sampled in two populations under the Faxinal System (Marmeleiro de Baixo and Barro Branco), in the municipality of Rebouças, PR and two others in conservation units (Flonas de Irati and Três Barras), located in Fernandes Pinheiro, PR and Três Barras, SC, respectively. The evaluation of the species associated with C. prismatica, considering the initial (pioneers and early secondary) and late (old secondary and climax), species was carried out in the areas of Faxinais, in the municipality of Rebouças, PR. In niche modeling, temperature and precipitation were the variables that most contributed to the construction of the models. In all periods and scenarios, the value obtained from AUC (Area Under the Curve) was 0.997. In the current scenario, the species has an area of suitability restricted to the FOM, with distribution limited to the Center-South of Paraná and the North of Santa Catarina. In the future scenario, there were reductions in areas suitable for the species in the optimistic (RCP4.5) and pessimistic (RCP8.5) scenarios. In the analysis of genetic diversity, eight ISSR markers (Inter Simple Sequence Repeat) were used, which were selected from 30 primers, which resulted in 67 polymorphic loci. The average genetic diversity within populations is 80.54%. The genetic diversity indexes of Shannon genetic diversity (I) and Nei (He) were 0.53 and 0.36, respectively. According to Nei's genetic identity, two groups are formed, one constituted by the populations of the Faxinal System and the other by the populations in the conservation units, which corroborated with the bayesiana analysis of the genetic structure of the populations, which indicated the existence of two distinct genetic groups (K = 2). In the survey of species associated with C. prismatica, 210 tree individuals were observed, divided into 16 botanical families and 29 species, the most associated species being: Curitiba prismatica, Casearia obliqua, Casearia sylvestris, Cinnamodendron dinisii, Ocotea odorifera and Casearia decandra. The Shannon diversity index (H') and Simpson dominance (C), considering all associated species, were 2.54 nats.ind-1 and 0.14, respectively. With higher diversity value and less dominance among late species (H' = 2.13 nats.ind-1 and C = 0.15 nats.ind-1 ). According to the competition rates of BAL, Glover & Hool (IGH) and Hegyi, competition under C. prismatica occurs with higher intensity in individuals with IGH ≤ 25 cm. Based on the results of Pearson's correlation analysis (rp) between competition indexes and annual period increments in diameter for the early and late species associated with C. prismatica, it can be seen that there were no significant correlations. Considering the diametric change between the related species, among the initial species, the highest probability of change exists in the class between 70 - 80 cm. Concerning late species, the probability of change is higher among individuals with IGH > 40 cm. The study contributes to improve the understanding of the autoecological characteristics of C. prismatica, supporting the management and conservation of the species.